2015
DOI: 10.1007/s11239-015-1274-7
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet efficacy of P2Y12 inhibitors (prasugrel, ticagrelor, clopidogrel) in patients treated with mild therapeutic hypothermia after cardiac arrest due to acute myocardial infarction

Abstract: Survivors after cardiac arrest (CA) due to AMI undergo PCI and then receive dual antiplatelet therapy. Mild therapeutic hypothermia (MTH) is recommended for unconscious patients after CA to improve neurological outcomes. MTH can attenuate the effectiveness of P2Y12 inhibitors by reducing gastrointestinal absorption and metabolic activation. The combined effect of these conditions on the efficacy of P2Y12 inhibitors is unknown. We compared the antiplatelet efficacies of new P2Y12 inhibitors in AMI patients afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 25 publications
1
33
0
1
Order By: Relevance
“…Our previous study documented strong and comparable antiplatelet efficacy for prasugrel and ticagrelor in the vast majority of patients with AMI after out-of-hospital cardiac arrest who were treated with mild therapeutic hypothermia. 24 Patients with cardiogenic shock are generally not included in randomized, clinical studies, and reported results on the efficacy and safety of the medications are very rare in this group of patients. Unfortunately, the results of the PRAGUE-18 study, given the small number of patients enrolled, cannot offer relevant arguments on the differences between benefits and risks of newer drugs for subgroups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study documented strong and comparable antiplatelet efficacy for prasugrel and ticagrelor in the vast majority of patients with AMI after out-of-hospital cardiac arrest who were treated with mild therapeutic hypothermia. 24 Patients with cardiogenic shock are generally not included in randomized, clinical studies, and reported results on the efficacy and safety of the medications are very rare in this group of patients. Unfortunately, the results of the PRAGUE-18 study, given the small number of patients enrolled, cannot offer relevant arguments on the differences between benefits and risks of newer drugs for subgroups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of studies were conducted under moderate TH (33°C) that lasted 24 hours, whereas mild (36°C) TH or different duration of TH was investigated to a lesser extent. Although some discrepancies exist among the published results, most studies demonstrate that moderate TH reduces P2Y 12 ‐mediated platelet inhibitory effect …”
Section: Th and P2y12 Inhibitorsmentioning
confidence: 96%
“…Briefly, the study showed that prasugrel and ticagrelor are highly effective in platelet inhibition in patients treated with mild TH after CA due to AMI but clopidogrel is not. It may suggest that administration of prasugrel or ticagrelor seems to be a more suitable option in this high‐risk group of acute patients …”
Section: Th and P2y12 Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations